Dinamika penegakan hak asasi manusia di Indonesia: Tantangan dan prospek di era modern - Ervianto, Moh Kevin (Maliki Interdisciplinary Journal, 2026)
The enforcement of human rights (HAM) in Indonesia is an issue that continues to experience dynamics along with the development of democracy, politics, law, and social change in the modern era. The 1998 Reformation marked the starting point for a major transformation in the state system through the strengthening of the constitution, the establishment of various human rights institutions, and the ratification of international human rights instruments. However, in practice, the enforcement of human rights still faces various complex structural and cultural challenges. This study aims to analyze the dynamics of human rights enforcement in Indonesia, identify the main challenges faced, and examine the prospects for human rights enforcement in the modern era. The method used is a qualitative approach with a literature study through analysis of laws and regulations, scientific journals, human rights institution reports, and various academic sources and other relevant data. The results of the study indicate that although Indonesia has made progress in the regulatory and institutional aspects of human rights, the implementation of enforcement is still not optimal. The main challenges include the weak resolution of past gross human rights violations, a culture of impunity, violence by the authorities, restrictions on civil liberties, threats against human rights defenders and journalists, and conflicts between economic interests and the protection of community rights, especially indigenous peoples and vulnerable groups. This study concludes that the enforcement of human rights in Indonesia is in a state of tension between the interests of democracy, political power, state security, and the demands of community justice. Therefore, a strong political commitment, continuous institutional reform, and active community participation are needed to realize the enforcement of human rights that is fair, democratic, and oriented towards the protection of human dignity in the modern era.